Apostasy from a Qur’anic and Hadith perspective: A study among converted Iranian in Malaysia / Gholamreza Nuei - Gholamreza , Nuei (2018)
Implementation of Islamic Law (Shariʿa) has always been of interest to the Islamic countries. Apostasy, as a Qurʾanic and Shariʿa decree, is among the subjects which contradicts with two subjects i.e., Human Rights as well as Freedom of Religion. Therefore, this study has tried to investigate the reasons and causes of apostasy in two different periods. In the other part, this study goes one step further to see the roots of conversion among Muslim communities during the early period of Islam on the basis of Qurʾanic, Ḥadīthī, and historical sources. The social, religious and personal reasons given for Muslim conversion in the Qurʾān and Ḥadīth are also investigated in details. This will pave the way to begin the next part in which conversion in the contemporary era is addressed. The researcher investigated a population of Iranians who are living in Malaysia, and they have converted to Christianity. This thesis focuses on this subgroup of “ex-Muslims” with the aim of providing a window into how they experience and justify their departure from Islam. A mixed method (qualitative-quantitative) has been conducted through which 13 people participated in an in-depth interview, and 45 people answered questionnaire. The research findings revealed some of the typical religious, social and personal reasons behind the conversion of this group of “ex-Muslims.” Finally, this study will compare the issue of “apostasy” in the early period of Islam and contemporary era in the light of Islamic scriptures and social contexts.